Daimler AG equity valuation - Lourenço, Gonçalo Lampreia Caeiro Cargaleiro (2020)
This dissertation aims to estimate the fair value of a Daimler AG share at the end of 2018, concluding with a buy, hold or sell recommendation. To accomplish this, the methodologies used are the Discounted Cash-Flow (DCF), the Dividend Discount Model (DDM) and Relative Valuation. Regarding this last model, the multiples used are the Price-Earnings Ratio, the Enterprise Value to EBITDA and the Enterprise Value to Sales. To introduce the assumptions taken, an overview of the firm is presented, as well as a sector and macroeconomic outlook. The firm overview comprises a description of Daimler’s business model, detailing its segments and recent performance. The sector outlook enlightens the future of the automotive industry and its renovating trends, whereas the macroeconomic outlook set out the basis for the future economic growth. The DCF model estimates a fair value for Daimler’s share of €93. Relative Valuation results were not consistent, as each multiple produces a different recommendation. The DDM retrieves a share price of €37, while the stock is trading at €59, as of April 2019. Hence, this dissertation produces a buy recommendation, based on the DCF, regarded as the most accurate model. Supporting this result, is Morningstar Equity Research that estimates a fair value of €85, yielding also a buy recommendation. A comprehensive comparison with Morningstar model is not possible due to lack of information provided.